Criteria for normal functioning of family - Maksimova, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article deals with the problem of finding criteria for the normal functioning of the family system. Shows the relationship between the causes of dysfunctions and resili potential family. The family which has normally functions – it is a family who responsibly performs its functions, so that needs are met in the growth and development of the family as a whole and each of its members. Failure or improper performance of family functions leads to the fact that the family is disharmonious (problem), and further dysfunctional. Dysfunction is dysfunction of the family – these are the features of its life, which complicate or hinder the implementation of family functions. Dysfunctional family in the broad sense is a system that determines the distortion in personal development, and hence maladaptive, deviant behavior or neurotic disorders of one or more of its members. There are results of a comparative study of subjective and objective factors of the violations of family relationships and the mechanisms of establishing harmonious relationships. Guidelines are developed for determining the need for appointment of social support of the family.